Mother-daughter Communication on Sexual and Reproductive Health: Correlations with Mothers’ Profile, Religiosity, and Attitudes towards Sex-ual and Reproductive Health - Chavez, Katrina Althea P.; Co, Maegan Helaena G.; Inocando, Trina Marie C.; Arcinas, Myla M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
With the surge in curiosity during adolescence, there is a greater emphasis on parents' inherent responsibility to guide their adolescents and aid in their positive development. This study sought to establish correlations of the quality of mother-daughter communication (MDC) with the mother's profile, religiosity, and attitude toward sexual and reproductive health (SRH) through the eyes of Grade 12 Senior High School female students, 18 years old and above, enrolled in a private university in Manila, Philippines. A total of 116 survey respondents were randomly selected for the study. Descriptive statistics and correlation tests were used to analyze the data. The findings indicated that the majority of the students' mothers are in their forties, earn a monthly income below the population average, and have three children. There was no statistically significant correlation between the age, income, and number of children variables with MDC quality. Respondents' mothers were highly religious and had a favorable attitude towards SRH. There was also no significant correlation between mothers' religiosity and MDC quality. Notably, a significant positive, strong correlation between MDC quality and mothers' attitudes towards SRH (r = .6589, n = 116, p = 8.94E-16) was found, implying that mothers' positive attitudes toward SRH improve the quality of MDC on SRH. The findings may guide efforts to improve mother-teen communication dynamics on SRH concerns and identify an effective strategy for enhancing quality teen SRH communication strategies; mothers' attitudes toward SRH are critical to the success of adolescent SRH programs.